Feeding Grain Sorghum to Swine - Robert O. Myer; Joel H. Brendemuhl; Daniel W. Gorbet (EDIS)
Revised! AS-33, a 7-page fact sheet by R.O. Myer, J.H. Brendemuhl, and D.W. Gorbet, explains how to use grain sorghum, an attractive alternative to corn for use in swine diets -- types of grain sorghum, nutrient composition, results of feeding trials, processing, and low-test-weight, sprout-damaged, and contaminated grain sorghum, and high-moisture grain sorghum. Includes tables comparing analyses of grain sorghum and other feedstuffs, and summary of experiments in Florida. Published by the UF Department of Animal Sciences, July 2006.